Attitudes towards the site: Bonet, tourism architectures and the conquest of Atamaría - Carcelén González, Ricardo; López Martínez, José M.; Aroca Vicente, Edith; García Martín, Fernando M. (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
Tourism architectures represented in the 1960s the ideal working context to deal with the new relationships between built architecture and the site, in short, nature. In this sense, Bonet Castellana was one of the Spanish architects who most significantly faced this scenario throughout his long career. The text brings us first of all to the actions of the architect in La Manga del Mar Menor in Murcia, where the flat condition of the site would determine the implantation strategies and the relationship between architecture and site in each case. This approach allows a better understanding of the attitudes towards the place developed later in Atamaría, which constitutes the main research in this work. Here, Bonet will carry out a series of tests in which the following project strategies will be addressed: architectures that emerge from the terrain, such as Bungalows B which, with their stepped section adapted to the terrain and the use of garden roofs, seem to disappear; architectures on the ground, such as Bungalows A or Apartamentos Mirador that assume the double strategy of plans suspended on a massive plinth adapted to the terrain; and, finally, architectures within the terrain, such as the unfinished Peters House in which, projected to be located at the highest point of the Atamaría mountain, it will be chosen to create an artificial horizontality by dismantling the original terrain.